REDESAIN PASAR CEPOGO DENGAN PENDEKATAN ARSITEKTUR KONTEKSTUAL DI BOYOLALI - Angela Ayu Desmaria; Hari Yuliarso; Tri Yuni Iswati (ARSITEKTURA, 2017)
Abstract: Pasar Cepogo is a public commercial centre in Cepogo. This traditional market is the preferred place to shop daily needs by the residents of Cepogo and people living in its surrounding area since it offers array of affordable prices. There are social aspects of the tradition manifested in the way bargains are settled. Yet, this market still has problems such as inconvenient environment, cluttered floor plan, uncharted activities, and decaying infrastructures. Based on these conditions, the design problem consists of creating a space to cater all activities in Pasar Cepogo and taking form fitting to its surrounding in order to maintain its existence as a traditional market. Redesign project of Pasar Cepogo aims to improve the condition of the market in order to provide convenient commercial space suiting present-day demand without leaving its traditional roots. Hence, contextual architecture approach is considered fit the notion. Contextual theme aspires to appropriate the redesigned building for its site, which concerns physical features, climate, culture, and local architecture aspects of the surrounding area. Physical features approach influence the site management adapted to the site conditions. Climate aspects approach is implemented into design response to the local climate, such as the use of  a high and sloping roof, tritisan, and cross ventilation. The cultural approach is actualized into the space management adapted to the context of activities in Pasar Cepogo. Local architecture approach is implemented into the form and appearance of the building, adjusting Java architecture and Hindu architecture that once evolved in Cepogo. Keywords: Contextual Architecture, Market Redesign, Traditional Market.